Effectiveness of clinical pathway in subjects with heart failure: A real-world study from Italian health claims (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Several process-of-care indicators have been developed and implemented to improve the quality of heart failure (HF) patients care. The aim of this study is to assess the relationship between a set of recommendations for HF care with measurable clinical outcomes, also in terms of outcomes that could be avoided.Methods: A retrospective cohort study was carried out on subjects with at least one hospitalization with a primary diagnosis of HF in 2007. Data were retrieved from healthcare utilization databases of Lombardy region (Italy). Exposure to selected recommendations (periodic control of echocardiogram and use of blockers of the renin-angiotensin system and beta-blockers) was recorded. All cause mortality and hospitalization with primary diagnosis of HF were considered as outcomes. Multivariable Cox models and Poisson model were fitted to estimate the exposure-outcome association.Results: Among 8207 cases of HF, those who adhered to none, one or all recommendations during the first year after diagnosis were 11%, 60% and 30%, respectively. Compared to patients who adhered to no recommendation, a significant mortality risk reduction of 24% (95% CI 17-31%) and 44% (36 52%) were observed for those who adhered to one and all recommendations, respectively. A significant reduction in the rate of re-hospitalizations in subjects adhered to at least one recommendation was also observed. A decreased trend in Population Attributable Fraction for death cases according to follow-up time was observed.Conclusion: A strict control of patients with HF through regular clinical examinations must be considered as fundamental for the reduction of mortality and re-hospitalizations.